Improvement of Napier Grass Silage Nutritive Value by Using Inoculant and Crude Enzymes from Trichoderma reesei and Its Effect on in Vitro Rumen Fermentation - Dea Justia Nurjana; S. Suharti; . Suryahadi (Media Peternakan, 2016)
This research was aimed to evaluate the effect of inoculant and crude enzyme of Trichoderma reesei on fermentation quality and rumen digestibility of napier grass silage. This research consisted of two stages. The first stage was fermentation quality using a completely randomized design with three treatments and six replications. The second stage was rumen fermentability using a randomized block design with three treatments and six replications. The treatments of both stages were: T0= control of napier grass silage (Hi-fer+), T1= control + T. reesei inoculant at the level of 2.13 x 107 cfu/kg, and T2= control + crude enzyme from T. reesei at the level of 11.4 unit/kg. Napier grass silage were kept at room temperature and opened 21 d after fermentation. The result of the first stage experiment showed that T2 decreased (P<0.01) dry matter, organic matter, crude fiber, and neutral detergent fiber (NDF) and also increased (P<0.05) crude protein, total digestible nutrient (TDN), pH, acetic acid, and propionic acid of napier grass silage while T1 decreased (P<0.01) NDF and increased (P<0.05) propionic acid. The result of the second stage experiment showed that there were no significant differences in rumen pH, in vitro dry matter and organic matter digestibility, total VFA, proportion of VFA, ratio of acetic to propionic acids, and also NH3. It is concluded that the addition of crude enzyme from T. reesei could improve fermentation quality of napier grass silage with decreasing NDF and increasing TDN but did not affect rumen fermentability.